(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2020)
Video is an audiovisual data that comprises of large number of frames.Â Analyzing and processing such large amount of data is difficult to many applications.Â Therefore, there is need for an effective video management scheme to manage these huge volume of video frames in order to provide easy access to the video content in lesser time.Â Keyframe extraction is the first step for video browsing, indexing and retrieval.Â Many techniques exist for the extraction of keyframes.Â However, some of the present techniques come with one or more limitations.Â In this paper, a brief review on the existing techniques is presented.Â Also, the merits and demerits of each technique is also stated.Â Â